Procedures for Verifying the Completeness of Customer Documents in the Application of Subsidized Mortgage Financing at BTN Syariah Probolinggo - Widya Dwy Anggraini (Universitas Nurul Jadid, 2025)
The Subsidized Home Ownership Credit (KPR) program is one of the government’s policy instruments aimed at improving access to home ownership for low-income communities. In its implementation, Islamic banks as financing distribution institutions play a strategic role in ensuring that the KPR application process is conducted in an accountable, transparent manner and in accordance with the principle of prudence. This study aims to analyze the procedures for verifying the completeness of customer documents in the application for subsidized KPR at BTN Syariah Probolinggo. The research employs a descriptive qualitative approach, with data collected through interviews, observations, and documentation. The findings indicate that the document verification procedure is carried out through several stages, starting from an initial administrative review, verification of the validity of identity and income documents, to an assessment of financing eligibility in accordance with Islamic principles. However, several obstacles remain, including incomplete customer documents, differences in understanding between customers and the bank, as well as limitations of digital systems in supporting the verification process. This study is expected to provide practical contributions to improving the effectiveness of subsidized KPR verification procedures in Islamic banking and to serve as a reference for future research.